X-ray diffraction results from IODP Hole 389-M0108B - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Results of X-ray diffraction (XRD) analyses from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). The offshore phase of this expedition took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai extquotesinglei, USA, followed by the onshore phase from 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. During the onshore phase a set of solid-phase samples, with a volume of approx. 10 cubic centimeters each, were taken from the work halves of core sections with the purpose to be later on split into aliquots for the following three analyses: X-ray diffraction, carbon analyses and X-ray fluorescence. Unprocessed samples were freeze-dried, ground and homogenized to a fine powder (<20 μm particle size) by ECORD Science Operator staff using a pestle and an agate mortar or a ball mill. The aliquots for XRD analysis were prepared with the Philips backloading system in the Crystallography and Geomaterials Research laboratories of the Geoscience Department at the University of Bremen (Germany). X-ray diffractograms were measured on a Bruker D8 Discover diffractometer. Mineral identification and semi-quantification were done using the Philips software X extquotesinglePert HighScore Version 1.2 (Degen et al., 2014, https://doi.org/10.1017/S0885715614000840) following concepts of Vogt (2009, https://doi.org/10.2204/iodp.proc.302.203.2009). Measurement results are all given in weight percent (wt%). For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025